2020
DOI: 10.26480/sfna.01.2020.42.47
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously Applied Moringa Leaf Extracts and Mixed Fertilizers in Soil to Improve Growth and Yield of Tomato (Lycopersicon Esculentum Mill.)

Abstract: Sustainable production of horticultural crops demand judicious application of integrated nutrient management and biostimulant like moringa leaf extract (MLE) which provides different macro and micronutrient including phytohormones. Two factors experiment was laid out in randomized complete block design (RCBD) with 3 replications to observe fertilizers and moringa leaf extract (MLE) effects on growth and yield of tomato. Fertilizer were F0 (control), F1 (vermicompost), F2 (inorganic fertilizer), F3 (2/3 F1 + 1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Similarly, Biswas et al (2020) found highest yield at this treatment in tomato. F 4 treatment gives the highest dry matter content (4.94%) and lowest was found from the F 1 treatment.…”
Section: Effect Of Different Types Of Fertilizers On Growth and Yield...mentioning
confidence: 56%
See 1 more Smart Citation
“…Similarly, Biswas et al (2020) found highest yield at this treatment in tomato. F 4 treatment gives the highest dry matter content (4.94%) and lowest was found from the F 1 treatment.…”
Section: Effect Of Different Types Of Fertilizers On Growth and Yield...mentioning
confidence: 56%
“…This reduces the need for a higher amount of inorganic fertilizer in crop production. Ultimately, application of reduced amount chemical fertilizer combined with judicious application of organic fertilizer sustain the quality of soil properties and product quality (Islam et al, 2017ab;Biswas et al, 2020) found that about 75% less amount inorganic fertilizer and judiciously incorporated vermicompost as organic fertilizer increased the 198% yield of tomato. Water is a natural resource and essential for crop production.…”
Section: Original Research Articlementioning
confidence: 99%
“…Ion imbalance can last a few days or even weeks in tender parts of the plants such as the bud [10]. It further induces secondary oxidative stress, leading to the inhibition of photosynthesis and metabolism and ultimately a deduction in plant yield [11]. Similar to high salinity, drought causes osmotic stress and secondary stress including oxidative stress, damage to cellular components, and metabolic dysfunction [10].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable growing with excessive inorganic fertilizers and inappropriate application of pesticides is now a common practice in Bangladesh to achieve higher yield. However, judicious combination of soil organic and inorganic fertilizers, and proper management might improve soil physical properties and nutrient towards enhance crop yield (Habib et al 2012;Afrin et al 2019;Biswas et al 2020;Farjana et al 2019). Sustainable management of soil and vegetable production are now getting enormous importance in Bangladesh in order to main soil environment.…”
Section: Introductionmentioning
confidence: 99%